A review of common psychoactive Substances in Emergency Medicine: Clinical Patterns and Diagnostic Strategies in the ED - Ogonowska, Paulina; Mazur, Urszula; Waszak, Julia; Adaśko, Grzegorz; Świda, Michał; Bazarewicz, Jakub; Michalska, Anna; Siwik, Marcin; Kubuj, Cezary; Dmowski, Daniel (Quality in Sport, 2025)
Introduction: The use of psychoactive substances in Europe has been steadily rising, resulting in a significant increase in emergency department (ED) visits related to acute intoxication. Substances such as cocaine, amphetamines, cannabinoids (including synthetic variants) and opioids, particularly potent analogues like fentanyl and nitazenes, pose complex diagnostic and therapeutic challenges in the emergency setting. Prompt recognition of clinical patterns and effective management are critical to reducing morbidity and mortality. Materials and Methods: This narrative review is based on an extensive analysis of current scientific literature, institutional reports (including EMCDDA and Euro-DEN), and clinical toxicology guidelines published between 2018 and 2025. Sources include observational studies, retrospective analyses, and expert recommendations focused on substance-related emergencies. The review discusses pharmacological mechanisms, clinical presentations, diagnostic strategies, and treatment protocols commonly employed in EDs. Summary: Each substance class is examined in terms of its pharmacodynamics, typical toxidromic features, and associated complications. The review highlights the diagnostic limitations of rapid toxicology screening and emphasizes the role of toxidrome recognition and structured emergency assessment tools. It also addresses the growing problem of polysubstance use, which complicates clinical presentation and requires careful, symptom-driven treatment approaches. Conclusions:The dynamic landscape of psychoactive substance use necessitates continuous updates in emergency care practices. Clinicians must rely on symptom-based management, targeted pharmacologic interventions such as naloxone or benzodiazepines, and vigilant patient monitoring. Broader availability of advanced toxicological testing and more prospective clinical data are essential for optimizing diagnosis and improving outcomes in substance-related emergencies.